Aportaciones corológicas a la flora vascular de las Alpujarras (Granada y Almeria, España). Chorological contributions for the vascular flora of the Alpujarras (Granada & Almeria, Spain) - Fuentes-Carretero, Julián Manuel (Acta Botanica Malacitana, 2014)
Chorological contributions for the vascular flora of the Alpujarras (Granada & Almería, Spain) Palabras clave. Plantas vasculares, corología, Andalucía, España. Key words. Vascular plants, chorology, Andalousie, Spain.